The Congress [videorecording (DVD)] - Burns, Ken, 1953-; Ives, Stephen; McCullough, David G.; Weisberger, Bernard A., 1922- (Ken Burns' America collection., 2013)
Portrait of the United States Congress. Filmmaker Ken Burns profiles an American institution whose ideals and actions affect us all. Employs historic film footage and interviews with insiders, including David Broker, Alistair Cooke and Cokie Roberts, to detail the personalities, events and issues that have animated Congress' first 200 years.